Chloropicrin-induced toxicity in the respiratory system. (1st May 2020) - Pesonen, M.; Vähäkangas, K.
Highlights: Chloropicrin is an irritating fumigant that poses health risk if inhaled. Respiratory system is the main target organ of acute toxicity. High levels of exposures injure respiratory tract, cause inflammation and lung edema. Molecular mechanism(s) of toxicity is complex and not fully understood. Symptoms and toxicity of chloropicrin resemble those caused by chlorine. Abstract: Chloropicrin is a volatile and reactive chemical that has been utilized as a warfare agent and a pesticide to fumigate soil against insects, fungi and nematodes. It poses a health risk to humans and animals if inhaled. The main source of chloropicrin exposure is occupational and occurs during its manufacture, transport and fumigation. Chloropicrin is toxic via all routes of exposure but the main route of systemic exposure is inhalation of the ambient air. Thus, the toxicity mainly affects the respiratory system. After a low level exposure, the first sign is irritation of the upper respiratory tract and eyes. Irritation is mediated by the sensory nerve fibers, which coordinate further activation of various protective reflexes. Chloropicrin-induced irritation is generally reversible but can alter airway responsiveness to other inhalation toxicants. Severe exposures cause injuries in the respiratory tract, inflammation, and even life-threatening edema. Much of the chloropicrin-caused symptoms and toxicity in the respiratory system displays similarities with those evoked by chlorine, which is also a breakdown product of chloropicrin. This review summarizes the latest information on chloropicrin with emphasis on the toxicity in the respiratory system. The data indicates that oxidative stress, modification of macromolecules, mutations, dysfunctions of cell organelles and cell death are involved in acute chloropicrin-induced toxicity in the respiratory system.